Coping Strategy to Counter the Challenges towards Implementation of Industry 4.0 in Thailand: Role of Supply Chain Agility and Resilience - Sakapas Saengchai; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
— Industry 4.0 is emerging as one of the most modern supply chain and manufacturing practices. Unfortunately, there are many challenges at organizational, legal, strategic and technological fronts which are barring implementation of industry 4.0 in manufacturing sector of Thailand. Such challenges can potentially be coped through supply chain agility and subsequently supply chain resilience as both provide enough sustainability to overall organization that can take care of implementation of Industry 4.0. This study has been conducted to determine the impact of supply chain agility on organizational, legal, strategic and technological challenges in the way of implementation of industry 4.0. Furthermore, mediating role of supply chain resilience has also been checked in relationship between agility and challenges. A questionnaire survey has been used to collect the data from Thailandâ€™s manufacturing sector employees and the same data was then analyzed through structural equation modeling for hypotheses testing. Results have interpreted significant impact of agility on challenges in implementation of Industry 4.0 while mediating role of resilience have also been flagged significant in respective relationship. Novelty in this research was testing agility and resilience as predictors to resolve challenges for Industry 4.0. This study will help different sectors of economy in a successful transition towards Industry 4.0.